Prevention of hypoglycemia by intermittent-scanning continuous glucose monitoring device combined with structured education in patients with type 1 diabetes mellitus: A randomized, crossover trial. (January 2023) - ,; Murata, Takashi; Hosoda, Kiminori; Kunihiro Nishimura,; Miyamoto, Yoshihiro; Sakane, Naoki; Satoh-Asahara, Noriko; Toyoda, Masao; Hirota, Yushi; Matsuhisa, Munehide; Kuroda, Akio; Kato, Ken; et al.
Highlights: Intermittent-scanning continuous glucose monitoring is useful to prevent hypoglycemia. Patient education regarding this device to prevent hypoglycemia remained unclear. A randomized cross-over trial was conducted in comparison to finger-prick glucose testing. Type 1 diabetes mellitus patients used the device to avoid impending hypoglycemia. By this intervention, time below range (<70 mg/dL) was significantly reduced by 21.9 %. Abstract: Aims: We conducted a randomized, crossover trial to compare intermittent-scanning continuous glucose monitoring (isCGM) device with structured education (Intervention) to self-monitoring of blood glucose (SMBG) (Control) in the reduction of time below range. Methods: This crossover trial involved 104 adults with type 1 diabetes mellitus (T1DM) using multiple daily injections. Participants were randomly allocated to either sequence Intervention/Control or sequence Control/Intervention. During the Intervention period which lasted 84 days, participants used the first-generation FreeStyle Libre (Abbott Diabetes Care, Alameda, CA, USA) and received structured education on how to prevent hypoglycemia based on the trend arrow and by frequent sensor scanning (≥10 times a day). Confirmatory SMBG was conducted before dosing insulin. The Control period lasted 84 days. The primary endpoint was the decrease in the time below range (TBR; <70 mg/dL). Results: The time below range was significantly reduced in the Intervention arm compared to the Control arm (2.42 ± 1.68 h/day [10.1 %±7.0 %] vs 3.10 ± 2.28 h/day [12.9 %±9.5 %], P  = 0.012). The ratio of high-risk participants with low blood glucose index >5 was significantly reduced (8.6 % vs 23.7 %, P  < 0.001). Conclusions: The use of isCGM combined with structured education significantly reduced the time below range in patients with T1DM.